Enhanced subglacial discharge amplifies Petermann Ice Shelf melting when ocean thermal forcing saturates - Abhay Prakash; Qin Zhou; Tore Hattermann; Nina Kirchner (Nature Communications)
Abstract Increased basal melting of the Petermann Ice Shelf is typically attributed to rising ocean temperatures. While subglacial discharge is known to intensify basal melt, the underlying mechanisms and their evolution in a warming climate remain unresolved. Using a 3-D numerical regional ice shelf–ocean model centered on the Petermann Fjord, we identify a regime shift in heat flux efficiency within the ice shelf cavity when discharge exceeds the current peak summer value. In this regime, thermal driving saturates, and discharge-intensified currents increase melt by enhancing shear-driven turbulent mixing across the ice shelf-ocean boundary layer. Increases in melt are most profound at the crests of basal channels, where vigorous meltwater confluence amplifies friction velocity. Challenging conventional attributions of increased ice shelf basal melting to ocean warming alone, our results demonstrate how atmospheric warming exacerbates ocean-driven melt processes and is likely to play a dominant role in amplifying future basal melt.